(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The present study seeks to establish the divergences produced in the reception of the script Viaje a la luna (1929) from Federico García Lorca and the cinematographic adaptation carried out by Frederic Amat (1998). Both stories-written and cinematographical-present dissimilarities in their actualization due to the difference between reader and observer. The displacements between both productions will be revised from the essential concepts of Wiser’s theory of the reading and R.Barthes’s structural sequences.